Lebih Dekat dengan Analisis Wacana - Ahmad, Ibnu (Mediator, 2007)
Discourse analysis gains more and more popularity in the field of media and communication studies. Focused on how media represented and framed the Text, it is the goals of discourse analysis to explore many implications underlie such representations. In order to utilize this approach effectively, a deeper knowledge concerning variety of methods and systematic ways on discourse theory was needed, as well as bins of critical and sociopolitical theories. The validity of discourse analysis will be judged by 7 (seven) indicators consisted of research aims, statement of problems, substantive theories being used, discourse theory being chosen, research paradigm being picked up, method being applied and analysis technique being employed.